The study of unreported igneous body, and its economic interest at Abu Zerriq area, north AlKufrah region, SELibya - Hweesh, Abdelraheem; El-Shari, Saad (Libyan Journal of Science &Technology, 2022)
This research deals with mineralogical and petrological investigation of an igneous intrusion located at Abu Zerriq area, with a distance of about 160 Km north to Al Kufrah town. Although the occurrence of igneous activities has not been reported before in this area, field inspections, followed by examination of thin sections under polarized microscope, have shown that this outcrop represents an igneous intrusion that comprises concentric rings of basalt and rhyolite. The basalt mainly is composed of laths of calcic plagioclase, relicts of altered olivine (partly serpentinized), quite abundant pyroxene crystals, and needle-like and anhedral opaque mineral (probably ilmenite). The economic interest of these rocks as a source of aggregates for construction is an important objective in this study. In order to determine the compressive strength of the rock samples, rock strength tests have been carried out. The results of these tests indicate that the studied rocks have high compressive strength, and they are much recommended for the purpose of civil constructions. The relatively large size of the material in this igneous body, and its close proximity to the constructed road, considerably increase its mining interest.